2007
DOI: 10.1161/strokeaha.106.480038
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Hydrocortisone Against Hyponatremia in Patients With Aneurysmal Subarachnoid Hemorrhage

Abstract: Background and Purpose-Hyponatremia is common after aneurysmal subarachnoid hemorrhage (SAH). It is caused by natriuresis, which induces osmotic diuresis and decreases blood volume, contributing to symptomatic cerebral vasospasm (SCV). Hypervolemic therapy to prevent SCV will not be efficient under this condition. We conducted a randomized controlled trial to assess the efficacy of hydrocortisone, which promotes sodium retention in the kidneys. Methods-Seventy-one SAH patients were randomly assigned after surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(60 citation statements)
references
References 7 publications
0
57
1
2
Order By: Relevance
“…It seems therefore unlikely that the administration of corticosteroids to 11 vs. 6 patients in the saline versus balanced group has influenced our results. Nevertheless, it has been demonstrated that corticosteroids can influence water and sodium balance after subarachnoidal hemorrhage [26,27]. Fluid balance was not associated with arterial hypertension or the use of steroids or norepinephrine.…”
Section: Discussionmentioning
confidence: 97%
“…It seems therefore unlikely that the administration of corticosteroids to 11 vs. 6 patients in the saline versus balanced group has influenced our results. Nevertheless, it has been demonstrated that corticosteroids can influence water and sodium balance after subarachnoidal hemorrhage [26,27]. Fluid balance was not associated with arterial hypertension or the use of steroids or norepinephrine.…”
Section: Discussionmentioning
confidence: 97%
“…Hydrocortisone has been shown to promote sodium retention in the kidney. Katayama and colleagues 37 randomly assigned 71 patients with subarachnoid hemorrhage to placebo or 1200 mg/d of hydrocortisone for 10 days. The primary outcome in this study was the prevention of hyponatremia.…”
Section: E284mentioning
confidence: 99%
“…15,16,18 Among these complications, delayed cerebral ischemia (DCI) remains an important cause of morbidity and death. 15 Many studies have investigated the prevention or treatment of DCI after SAH.…”
mentioning
confidence: 99%